2005
DOI: 10.1063/1.1879852
|View full text |Cite
|
Sign up to set email alerts
|

A dissipative particle dynamics description of liquid-crystalline phases. I. Methodology and applications

Abstract: Simulations of nematic and smectic mesophases based on a dissipative particle dynamics approach are discussed. Mesogenic units are built in the form of standard semirigid bead-spring chains. It is shown that nematic phases can be formed for chains containing at least eight beads, provided that the conservative soft-repulsive potential between nonconnected beads is sufficiently strong. Smectic phases are observed only by modifying the repulsive interaction between the main-chain and terminal beads. The simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Nanorods are simulated as rigid bodies in the NVE ensemble using an algorithm by Miller et al 57 Their correct temperature is maintained through the interactions with the thermostated polymeric DPD liquid surrounding them. It is worth noting that semi-rigid mesogens can be also simulated with DPD using an additional spring force between their first and last particles 58 or by introducing angle potentials. 59 For the sake of comparison we perform some simulations by replacing nanorods with flexible chains consisting of N R = 5 particles of R type.…”
Section: A Dissipative Particle Dynamicsmentioning
confidence: 99%
“…Nanorods are simulated as rigid bodies in the NVE ensemble using an algorithm by Miller et al 57 Their correct temperature is maintained through the interactions with the thermostated polymeric DPD liquid surrounding them. It is worth noting that semi-rigid mesogens can be also simulated with DPD using an additional spring force between their first and last particles 58 or by introducing angle potentials. 59 For the sake of comparison we perform some simulations by replacing nanorods with flexible chains consisting of N R = 5 particles of R type.…”
Section: A Dissipative Particle Dynamicsmentioning
confidence: 99%
“…In the case of the A 1 B 3 polymer a lamellar phase is observed at T * = 1.0; the low value of the order parameter and the fact that the middle eigenvalue of the order tensor (S 0 ) is significantly larger than 0 suggests that the polymer chains within each layer are well ordered but the orientation of each layer is independent of the others. It is noticeable that none of the polymers studied exhibits a nematic phase, which has been observed in DPD simulations of rigid and semi-rigid rods [42,36]. It is possible that the transition to positionally ordered phases preempts the isotropic-nematic transition.…”
Section: Resultsmentioning
confidence: 93%
“…Unlike in experimental studies, a nematic phase is not observed in any of the systems considered in this work. Nematic phases have been observed in DPD simulations [36] and it is likely that in the systems studied the nematic window is vanishingly small or that translational ordering preempts the formation of the nematic phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherent in the DPD work is the employment of underlying ultra-soft-potentials, allowing particles to pass through each other and thereby improving equilibration times greatly. Such technique have recently been exploited by Levine et al [151] and Gomes and co-workers [152] to study nematic and smectic mesophases.…”
Section: Helical Twisting Powersmentioning
confidence: 99%